METODE PEMBELAJARAN MULTISENSORI DALAM MEMPENGARUHI KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN DI TK. AL-ISLAM MARON GENTENG BANYUWANGI TAHUN AJARAN 2018-2019 - Elok Faeka Humma; Ellyana Ilsan Eka Putri (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This study aims to find out about the influence of multisensory methods in improving the language skills of children aged 5-6 years in Al-Islam kindergarten Maron Genteng Banyuwangi in the 2018-2019 school year. Explaining about the 7 subjects studied 5 boys and 2 girls and the activities carried out in the school related to the multisensory method. This study uses descriptive qualitative research methods. The technique in collecting data here uses data triangulation in the form of observation, interviews and documentation, as well as source triangulation. The results of this study can be concluded that the multisensory learning method influences the language skills of children aged 5-6 years in the Al-Islam kindergarten Maron Banyuwangi evidenced by not only facilitating children's activities in school but also facilitating the activities of children at home. This is evidenced by interviews with parents from each research subject.